Consumption bundle aggregation in poverty measurement: Implications for poverty and its dynamics in Uganda - Van Campenhout, Bjorn; Ssekabira, Haruna; Aduayom, Dede H. (United Nations University, 2014)
Official poverty figures in Uganda are flawed by the fact that the underlying poverty lines are based on a single national food basket that was constructed in the early 1990s. In this paper, we estimate a new set of poverty lines that accounts for the widely divergent diets throughout the country using the latest available household survey. Using these updated poverty lines, we then look at poverty dynamics using four waves of the Uganda National Panel Survey. We classify households into categories depending on their change in poverty status over time and relate this to characteristics that are likely to change only slowly. This enables us to explore the characteristics of households that, for instance, grow out of poverty and how they differ from households that appear to be trapped in poverty. Our approach generates poverty measures that are more credible from a theoretical point of view and are more in line with what other researchers find.